Phidon abismus sp. nov. from Patagonian forests of Argentina (Blattaria: Pseudophyllodromiidae) - Bramardi, Martina A.; Moccia, Tobías; Kun, Marcelo E. (Zootaxa, 2023)
Phidon abismus sp. nov. is described from north-western Patagonian forests in Argentina. The specimens were collected under dead tree bark of Austrocedrus chilensis, Nothofagus dombeyi and Nothofagus pumilio. A detailed description of the male including abdominal apex, genitalia, tegmen and wing venation and front femur armament type B2 is provided as well as a description of the A type oviparity. The genus Phidon is recorded from Argentina for the first time. The key of Rehn (1933) for the known males of the genus is updated.